Management of Ramadhan Bazaar in Empowering the Community's Economy on the Waqf Land of the Baitul Khoir Grand Mosque in Tulungagung - Kalimah, Siti; M. Ali Tamrin (Al-Kharaj: Journal of Islamic Economic and Business, 2025)
This article discusses the management of the Ramadan Bazaar held on the waqf land of the Baitul Khoir Grand Mosque in Tulungagung, as a means of empowering the local Muslim community. The bazaar serves not only religious and social functions but also acts as a productive initiative to optimize waqf assets for community welfare. Managed through systematic planning, organizing, implementation, and controlling stages, this activity represents a practical application of productive waqf. This study employs a qualitative descriptive method with a case study approach. The data collection technique involved structured interviews with mosque administrators and business actors involved in the bazaar, as well as the documentation of ongoing activities. The results indicate that the Ramadan Bazaar has a positive impact on the local economy, while also strengthening the mosque’s social and spiritual role. However, challenges remain in management and program sustainability. The study recommends a productive waqf-based bazaar management model as an alternative strategy for mosque-based economic empowerment, emphasizing the need for collaboration among mosque administrators, the community, and supporting institutions.